Design and development of a low power charge controller / Mohd Saiful Hafizi Zakaria - Zakaria, Mohd Saiful Hafizi (2013)
Converter is an electrical circuit that commonly used in power electronics devices. This converter used to convert electrical energy from one form to another, from the source to load with highest efficiency, high availability and high reliability with the lowest cost, smallest size and weight. There are many types of power electronics converters such as rectifier (AC to DC), chopper (DC to AC) and inverter (DC to AC). In this charge controller project, the converter used is dc to dc buck converter that had been design using PSIM simulation software. This converter is using Photovoltaic (PV) input and battery 12 V as the output. Photovoltaic is one of the renewable energy resources that recently have become broader in nowadays technology. By using microchip that is microcontroller PIC16F873, the Programmable Interface Controller (PIC) will control the duty cycle of the MOSFET in the buck converter circuit. The characteristic of the photovoltaic also is determined so the PV used in the circuit is correctly design. This PIC is programmed using MikroBasic Pro software. Liquid Crystal Display (LCD) is used to display the value of the voltage, current, power and state of the battery that had been program using the same PIC.